Structure assembly regularities in vapour-deposited gold–fullerene mixture films. Issue 4 (10th March 2020) - Lavrentiev, V.; Motylenko, M.; Barchuk, M.; Schimpf, C.; Lavrentieva, I.; Pokorný, J.; Röder, C.; Vacik, J.; Dejneka, A.; Rafaja, D.
Abstract : Three compositional intervals x (R1, R2 and R3) with different mechanisms of nanostructure self-assembling in the Au x C60 mixture films (0 < x < 30) have been established. Abstract : Self-assembly is an attractive phenomenon that, with proper handling, can enable the production of sophisticated hybrid nanostructures with sub-nm-scale precision. The importance of this phenomenon is particularly notable in the fabrication of metal–organic nanomaterials as promising substances for spintronic devices. The exploitation of self-assembly in nanofabrication requires a comprehension of atomic processes creating hybrid nanostructures. Here, we focus on the self-assembly processes in the vapour-deposited Au x C60 mixture films, revealing the exciting quantum plasmon effects. Through a systematic characterization of the Au x C60 films carried out using structure-sensitive techniques, we have established correlations between the film nanostructure and the Au concentration, x . The analysis of these correlations designates the Au intercalation into the C60 lattice and the Au clustering as the basic processes of the nanostructure self-assembly in the mixture films, the efficiency of which strongly depends on x . The evaluation of this dependence for the Au x C60 composite nanostructures formed in a certain composition interval allows us to control the size of the Au clusters and the intercluster spacing by adjusting the Au concentration only. This study represents the self-assembled Au x C60 mixtures as quantum materials with electronic functions tuneable by the Au concentration in the depositing mixture.